PERANCANGAN KOMIK SUPERHERO YANG DIADAPTASI DARI TARI TOPENG INDONESIA DENGAN MEDIA KOMIK DIGITAL - Widya Oktaviani, Fania; Rangga Putra, Damar (Universitas Budi Luhur, 2025)
The rapid progress of the times has influenced the lack of interest of the young generation in Indonesian culture, one of which is the Indian Mask Dance. This design employs qualitative techniques The Double Diamond to craft a digital comic based on the Indonesian mask dance, featuring superheroes as protectors for the Indonesian people. The masked dance represented several islands in Indonesia, including the Huda-Huda Dance from Sumatra Island, the Sinok Dance from Java Island, the Telek Dance from Bali Island, Jipae from Irian Island, and the Kemindu Dance from Kalimantan Island. The benefits of this research can be concluded to include adding enthusiasm, inspiring the younger generation to add insight, and learning more about Indonesian culture.